Experimental Study of the Effect of Reflection Mirrors Orientation on the Performance of Solar Still - Abass Z. Salman; Saad T. Hamidi (Journal of Engineering and Sustainable Development, 2012)
The present experimental work is a study of solar still with reflected mirrors. The solar radiation was calculated mathematically for angles ranging from 9o to 30o with 15o increment for reflected mirrors and from 0-45o with 5o increment for glass cover. Experimental analysis showed that the best angle that intercept the maximum amount for solar radiation at the angle 85o for reflected mirrors at the south-north orientation of solar still which indicates that as the slop of mirrors increase the average solar radiation decreases. Also the glass cover is inclined about 40o. The study included the experimented test for the angle which may not permit the condensate to drip back into the basin. It was found to be 11o.